2014
DOI: 10.1111/jpy.12205
|View full text |Cite
|
Sign up to set email alerts
|

Misleading morphologies and the importance of sequencing type specimens for resolving coralline taxonomy (Corallinales, Rhodophyta): Pachyarthron cretaceum is Corallina officinalis

Abstract: Coralline red algae play a key role in the ecology of near shore marine ecosystems and are increasingly being used to study the effects of climate change in the marine environment. Corallines are very difficult to identify to species, and even to genus, using morpho-anatomy, likely complicating studies of their ecology, physiology, and biodiversity. We sequenced a 296 base pair fragment of chloroplast DNA from a 187-year-old isolectotype specimen of Pachyarthron cretaceum, a morphologically distinct geniculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 32 publications
1
57
0
4
Order By: Relevance
“…Given these difficulties, coralline algal researchers now combine examination of type material and morphologically concordant material from type localities (e.g. topotypes) using DNA sequences or morphology to verify names (Gabrielson et al, 2011;Hind et al, 2014). In the present study, type material of rhodolith-forming species and/or other morphologically similar material from type localities was analysed using scanning electron microscopy (SEM) and reproductive information.…”
Section: Phylogenetic Analysis Of Rhodolith Formation In the Corallinmentioning
confidence: 99%
“…Given these difficulties, coralline algal researchers now combine examination of type material and morphologically concordant material from type localities (e.g. topotypes) using DNA sequences or morphology to verify names (Gabrielson et al, 2011;Hind et al, 2014). In the present study, type material of rhodolith-forming species and/or other morphologically similar material from type localities was analysed using scanning electron microscopy (SEM) and reproductive information.…”
Section: Phylogenetic Analysis Of Rhodolith Formation In the Corallinmentioning
confidence: 99%
“…Kim et al (2007) examined phylogenetic relationships within the Janieae and concluded that it contains a single genus, Jania, in which species formerly referred to Cheilosporum and Haliptilon should be included. The Corallineae, including the genera Alatocladia, Arthrocardia, Bossiella, Calliarthron, Chiharaea, Corallina, Ellisolandia, Johansenia, Masakiella, Pachyarthron and the species Pseudolithophyllum muricatum (Foslie) Steneck & R.T. Paine, have been the focus of several recent phylogenetic studies addressing issues of diversity, misidentification and taxonomic relationships (Robba et al 2006;Walker et al 2009;Gabrielson et al 2011;Martone et al 2012;Brodie et al 2013;Hind & Saunders 2013a, b;Hind et al 2014). Important for such work is the method outlined by Gabrielson et al (2011), in which species identity is approached through the application of molecular methods to systematic problems by focusing on sequences obtained from type specimens of generitype species and other species included in each genus.…”
Section: Introductionmentioning
confidence: 99%
“…Since Saunders (2005) pioneered the use of DNA barcoding for red macroalgae, which was soon adopted by Robba et al (2006), there has been an increase in the acceptance of molecular techniques as a tool for species identification. Since then the use of molecular identification has revealed cryptic diversity in all orders of red algae tested (Robba et 5 al., 2006), highlighting the misidentification of species due to misleading morphologies (Hind et al, 2014), and helped to uncover evolutionary history (Hind & Saunders, 2013). Species identification studies of maerl beds in Europe (Carro et al, 2014;Pardo et al, 2014;Hernández-Kantún et al, 2015;Peña et al,.…”
Section: Crouan and H Crouan Andmentioning
confidence: 99%